Defectors' intolerance of others promotes cooperation in the repeated public goods game with opting out - Křivan, Vlastimil; Cressman, Ross (Scientific reports, 2020)
The theoretical and experimental research on opting out (also called conditional dissociation) in social dilemmas has concentrated on the effect this behavior has on the level of cooperation when used against defectors. The intuition behind this emphasis is based on the common property of social dilemmas that individuals are worse off the more their opponents defect. However, this article shows clearly that other opting out mechanisms are better at increasing cooperative behavior. In fact, by analyzing the stable Nash equilibria for the repeated multi-player public goods game with opting out, our results provide a strong argument that the best opting out rule is one whereby the only groups that voluntarily stay together between rounds are those that are homogeneous (i.e., those groups that are either all cooperators or all defectors), when these groups stay together for enough rounds. This outcome emerges when defectors are completely intolerant of individuals who cooperate (e.g., defectors exhibit xenophobic behavior toward cooperators) and so opt out whenever their group has a cooperator in it. The strong preference by defectors to be with like-minded individuals causes all heterogeneous groups to disband after one round.
Keywords: Cooperative Behavior; Games, Recreational; teorie her; interpersonální vztahy; kooperační chování; Game Theory; lidé; Interpersonal Relations; teoretické modely; rekreační hry; Group Processes; skupinové procesy; Models, Theoretical; Humans